Geraniin inhibits oral cancer cell migration by suppressing matrix metalloproteinase‐2 activation through the FAK/Src and ERK pathways. Issue 10 (11th June 2019) - Yeh, Chia‐Ming; Hsieh, Ming‐Ju; Yang, Jia‐Sin; Yang, Shun‐Fa; Chuang, Yi‐Ting; Su, Shih‐Chi; Liang, Meng‐Yuan; Chen, Mu‐Kuan; Lin, Chiao‐Wen
Abstract: Geraniin has been reported to have numerous biological activities, including antiviral, antihypertensive, antihyperglycaemic, liver protective, antidiabetic, and apoptotic activities. However, the anti‐migration effects of geraniin on oral cancer remain elusive. In this study, we revealed the potential antitumor mechanisms of geraniin through the inhibition of the migration and invasion of human oral cancer cell lines SCC‐9 and SCC‐14. The results of gelatin zymography and Western blot assays revealed that geraniin significantly reduced the activity and expression of matrix metalloproteinase‐2 (MMP‐2) of oral cancer cells in a concentration‐dependent manner. Furthermore, geraniin potently suppressed the phosphorylation of focal adhesion kinase (FAK), Src, and extracellular signal‐regulated kinase (ERK)1/2 but did not affect the phosphorylation of p38 mitogen‐activated protein kinase (MAPK) and c‐Jun N‐terminal kinase 1/2. Moreover, blocking the MAPK/ERK1/2 pathway significantly enhanced the anti‐migration ability of geraniin in oral cancer cells. In conclusion, we demonstrated that geraniin inhibits the motility of SCC‐9 and SCC‐14 cells in vitro through a molecular mechanism that involves the attenuation of MMP‐2 expression and activity mediated by decreased FAK/Src and ERK1/2 pathways.